Condition for infinite sum

Algebra Level 3

1 2 + 4 x + 1 ( 2 + 4 x ) 2 + 1 ( 2 + 4 x ) 3 + \large \frac 1{2+4x} + \frac 1{(2+4x)^2} + \dfrac 1{(2+4x)^3} + \ldots

Above is a geometric series. Given that the condition for infinite sum to converge is x < a x > b x < a \cup x > b . Find ( a b ) 2 \left(\dfrac ab \right)^2 .


The answer is 9.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Aug 25, 2018

For the given series to converge, 2 + 4 x > 1 |2+4x| > 1 { 2 + 4 x > 1 x > 1 4 2 + 4 x < 1 x < 3 4 \implies \begin{cases} 2+4x > 1 & \implies x > - \frac 14 \\ 2+4x < -1 & \implies x < - \frac 34 \end{cases} . Therefore, ( a b ) 2 = ( 3 4 1 4 ) 2 = 9 \left(\dfrac ab \right)^2 = \left(\dfrac {-\frac 34}{-\frac 14} \right)^2 = \boxed 9 .

Munem Shahriar
Aug 24, 2018

Assume 1 2 + 4 x + 1 ( 2 + 4 x ) 2 + 1 ( 2 + 4 x ) 3 + = S \dfrac 1{2+4x} + \dfrac 1{(2+4x)^2} + \dfrac 1{(2+4x)^3} + \ldots = S .

Here, first term, u 1 = 1 2 + 4 x u_1 = \dfrac 1{2+4x} and second term u 2 = 1 ( 2 + 4 x ) 2 u_2 = \dfrac 1{(2+4x)^2} .

So general ratio, r = u 2 u 1 = 1 ( 2 + 4 x ) 2 1 2 + 4 x = 1 ( 2 + 4 x ) 2 × ( 2 + 4 x ) = 1 2 + 4 x . r = \dfrac{u_2}{u_1} = \dfrac{\frac 1{(2+4x)^2}}{\frac 1{2+4x}} = \dfrac 1{(2+4x)^2} \times (2+4x) = \dfrac 1{2+4x}.

S S will only have a infinite sum if 1 < r < 1 -1 < r < 1 . So 1 < 1 2 + 4 x < 1 -1 < \dfrac 1{2+4x} < 1 . Now,

1 < 1 2 + 4 x 1 2 + 4 x > 1 2 + 4 x < 1 4 x < 3 x < 3 4 \begin{aligned} -1 & < \dfrac 1{2+4x} \\ \Rightarrow \dfrac 1{2+4x} & > -1 \\ \Rightarrow 2 + 4x & < -1 \\ \Rightarrow 4x & < -3 \\ \implies x & < -\dfrac 34 \\ \end{aligned}

Again,

1 2 + 4 x < 1 2 + 4 x > 1 4 x > 1 x > 1 4 \begin{aligned} \dfrac 1{2+4x} & < 1 \\ \Rightarrow 2+4x & > 1 \\ \Rightarrow 4x & > -1 \\ \implies x & > -\dfrac 14 \\ \end{aligned}

So a = 3 4 a = -\dfrac 34 and b = 1 4 b = -\dfrac 14 . Hence ( a b ) 2 = ( 3 4 1 4 ) 2 = ( 3 4 × 4 ) 2 = 3 2 = 9 \left(\dfrac ab \right)^2 = \left(\dfrac{-\frac 34}{-\frac 14}\right)^2 = \left(\dfrac 34 \times 4 \right)^2 = 3^2 = \boxed 9 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...